Performance investigation of a combined biomass gasifier-SOFC plant for compressed hydrogen production - Yuksel, Yunus Emre; Ozturk, Murat; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
As an alternative, clean and sustainable solution, a biomass-based integrated power plant is designed and studied both thermodynamically and parametrically. Due to the environmental, economic and performance related advantages, the design of multigeneration energy plants is now increasing and becoming widespread technology. Biomass, which is one of the renewable power sources, is selected for the plant to be more sustainable and environmentally friendly. The proposed system using biomass as an energy source consists of several sub-plants integrated to utilize the waste thermal energy and to generate useful products which are electricity, hydrogen, fresh and hot water, heating, and cooling. In this paper, comprehensive work is carried out for plant modeling and simulation. The thermodynamic assessment results reveal that both energetic and exergetic effectiveness of the whole plant are 56.17% and 52.83%, which are affected positively by varying the reference state conditions, combustor temperature, biomass gasifier temperature, SOFC temperature and pressure, and biomass mass flow rate. In addition, the lowest energy and exergy efficiencies occur in the ORC combined ejector refrigeration cycle with 21.87% and 18.26%, respectively. (C) 2020 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Thermodynamic; Energy efficiency; Exergy efficiency; Biomass; SOFC; Compressed hydrogen; THERMODYNAMIC ANALYSIS; INTEGRATED-SYSTEM; EXERGY ANALYSIS; ENERGY SYSTEM; MULTIGENERATION; POWER; GASIFICATION; CYCLE; HEAT; Chemistry; Electrochemistry; Energy & Fuels